Youth as cultural mediators in ecological literacy: A moronene-based participatory campaign in a post-artisanal and small-scale gold mining community - Basri Basri; Masayuki Sakakibara; Hendra Prasetia; La Sahara; Chitra Dewi; Nanang Rahmadani (Interaction, Community Engagement, and Social Environment, 2026)
Background: Artisanal and small-scale gold mining, has caused river pollution, deforestation, and ecological disruption while weakening the transmission of Moronene ecological knowledge across generations. This study addresses that gap by examining how SEPAKAT’s (a local youth organization) Moronene-based ecological literacy campaign was designed, implemented, and experienced in improving ecological knowledge, strengthening youth-mediated intergenerational knowledge transfer, and identifying its enabling factors, constraints, and practical implications in a post-ASGM context. Methods: This study examined a youth-led ecological literacy campaign developed by SEPAKAT using participatory action research and an embedded mixed-methods design. The proposed model was validated through contextual/content validation with local stakeholders, process validation through triangulation of interviews, focus group discussions, observations, campaign documents, and participation records, and outcome validation using a one-group pretest–posttest design involving 50 participants . Quantitative data were analyzed using descriptive statistics and paired-sample t-tests, while qualitative data were analyzed thematically and integrated through triangulation. Findings: The findings show that the campaign was implemented in four sequential phases, with the largest proportion of time allocated to the Story Space and workshops (34%), indicating the central role of intergenerational dialogue and collaborative learning. Ecological knowledge improved significantly across all domains, with overall scores increasing from 2.67 ± 0.61 to 4.05 ± 0.49 (mean difference = 1.38; 51.7%; t = 9.57; p < 0.001). Youth mediation also improved significantly, particularly in translating Moronene ecological knowledge into educational media (mean difference = 1.58; 59.8%; t = 10.08; p < 0.001). The intervention was most strongly enabled by the cultural legitimacy of Moronene values (4.42 ± 0.51; 88%) and SEPAKAT’s leadership (4.28 ± 0.56; 84%), but was constrained by limited resources and logistical challenges. Conclusion: The study concludes that youth-led, culturally grounded ecological literacy can support ecological recovery, environmental learning, and intergenerational continuity in post-ASGM communities. Novelty/Originality of this article: The novelty of this article lies in demonstrating how youth-led intergenerational co-production operationalizes indigenous ecological knowledge within a structured ecological literacy model in a post-extractive setting.